Florentina Esteves and Orlanda Amarílis in dialogue: a proposal for teaching literature from a decolonial perspective - Silva, Angela Glaucia da; Silva, Ezilda Maciel da (The ESPecialist, 2024)
This article presents a decolonial didactic proposal for teaching the short stories "Que Jiquitaia!" by Florentina Esteves (1990) and "Desencanto" by Orlanda Amarílis (1991). The conception adopted is that of Iris Amâncio and Miriam Jorge (2008). In this way, the aim is to propose a transgressive, humanizing and transformative teaching practice through which students acquire “literature as literature”. The methodology is based on a bibliographical study. The conclusion indicate that teaching, learning, analyzing and interpreting the short stories of Esteves and Amarílis, in school, ensure that students practice literary reading as a humanizing, emancipating and polyphonic act of Acre and Cape Verde literature.